The Impact of Micronutrients-Calcium, Vitamin D, Selenium, Zinc in Cardiovascular Health: A Mini Review - Narayanam, Harini; Chinni, Suresh V.; Samuggam, Sumitha (Frontiers in Physiology, 2021)
The role of micronutrients in health and disease has increased the curiosity and interest among researchers. The prime focus of this review is the significance of trace elements- calcium, vitamin D, selenium and zinc with cardiovascular health. WHO identified cardiovascular diseases (CVD) as the leading cause of deaths globally. Identifying the risk factors that could be modified and creating new treatment strategies remains to be the main concern for CVD prevention. The data that showed the relationship between trace elements and various ways in which they may contribute to cardiovascular health and disease from clinical trials and observational studies were collected from databases such as PubMed and Embase. Based on these collected data, it shows that either high or low circulating serum levels can be associated with the development of cardiovascular diseases. Micronutrients through diet contribute to improved cardiac health. However, due to our current lifestyle, there is a huge dependency on dietary supplements. Based on the observational studies, it is evident that supplements cause sudden increase in the circulating levels of the nutrients and result in cardiovascular damage. Thus, it is advisable to restrict the use of supplements, owing to the potent risks it may cause. In order to understand the exact mechanism between micronutrients and cardiac health, more clinical studies are required.